CRISPR interference for sequence-specific regulation of fibroblast growth factor receptor A in Schistosoma mansoni - Du, Xiaofeng; McManus, Donald P.; French, Juliet D.; Collinson, Natasha; Sivakumaran, Haran; MacGregor, Skye R.; Fogarty, Conor E.; Jones, Malcolm K.; You, Hong (Frontiers in Immunology, 2023)
Employing the flatworm parasite Schistosoma mansoni as a model, we report the first application of CRISPR interference (CRISPRi) in parasitic helminths for loss-of-function studies targeting the SmfgfrA gene which encodes the stem cell marker, fibroblast growth factor receptor A (FGFRA). SmFGFRA is essential for maintaining schistosome stem cells and critical in the schistosome-host interplay. The SmfgfrA gene was targeted in S. mansoni adult worms, eggs and schistosomula using a catalytically dead Cas9 (dCas9) fused to a transcriptional repressor KRAB. We showed that SmfgfrA repression resulted in considerable phenotypic differences in the modulated parasites compared with controls, including reduced levels of SmfgfrA transcription and decreased protein expression of SmFGFRA, a decline in EdU (thymidine analog 5-ethynyl-2'-deoxyuridine, which specifically stains schistosome stem cells) signal, and an increase in cell apoptosis. Notably, reduced SmfgfrA transcription was evident in miracidia hatched from SmfgfrA-repressed eggs, and resulted in a significant change in miracidial behavior, indicative of a durable repression effect caused by CRISPRi. Intravenous injection of mice with SmfgfrA-repressed eggs resulted in granulomas that were markedly reduced in size and a decline in the level of serum IgE, emphasizing the importance of SmFGFRA in regulating the host immune response induced during schistosome infection. Our findings show the feasibility of applying CRISPRi for effective, targeted transcriptional repression in schistosomes, and provide the basis for employing CRISPRi to selectively perturb gene expression in parasitic helminths on a genome-wide scale.